2013
DOI: 10.1021/jf401712d
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Carrageenan at Different Stages of Winemaking for White Wine Protein Stabilization

Abstract: Carrageenan added at different stages of winemaking was assessed for its protein removal and impact on wine heat stability and on the chemical and sensorial profile of the wines. Carrageenan was added to a Semillon during fermentation and after fermentation and to finished wines, and the effect of each addition was compared to that of bentonite fining at the same time point. Data on protein concentration, heat stability, and bentonite requirement indicate that when added at the correct dosage carrageenan was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…The cooling temperature reported for the heat test also varies in the literature and this may influence the amount of haze formed in the heat test. The most commonly reported cooling temperature is 0°C in an ice bath, 4°C in a fridge or 20°C in a temperature‐controlled water bath (Pocock and Waters , Marangon et al , Jaeckels et al ). To investigate the impact of cooling temperature on haze formation, a range of unfined white wines was selected: a RIE, two CHAs (CHA1 and CHA2) and a SEM (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling temperature reported for the heat test also varies in the literature and this may influence the amount of haze formed in the heat test. The most commonly reported cooling temperature is 0°C in an ice bath, 4°C in a fridge or 20°C in a temperature‐controlled water bath (Pocock and Waters , Marangon et al , Jaeckels et al ). To investigate the impact of cooling temperature on haze formation, a range of unfined white wines was selected: a RIE, two CHAs (CHA1 and CHA2) and a SEM (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…During this test, wines are heated for a specified time, cooled and the amount of haze produced before and after heating is recorded. The conditions recommended for heating and cooling vary widely and include heating at 80°C for 2 h then cooling at 4°C for 16 h (Pocock and Waters ), or cooling at 0°C for 2 h (Marangon et al , Chagas et al , Salazar et al ), or cooling to 4°C for 2 h (de Bruijn et al ). Other methods include heating to 80°C for 3 h followed by cooling at 20°C for 0.5 h (Jaeckels et al , Meier et al ); heating at 80°C for 6 h then cooling at 4°C for 16 h (Pocock and Rankine , Batista et al , Vincenzi et al , Benucci et al ); 80°C for 30 min with no cooling time specified (Gabrielli et al ); 90°C for 1 h then cooling at 4°C for 18 h (Giese et al ), or heating samples to 30–80°C for 6 h and cooling at 4°C for 16 h with the change in turbidity monitored at different temperature values (Lambri et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were heated at 80°C for 2 h in a thermomixer and subsequently cooled in ice for 2 h. After equilibration at ambient temperature, the increase in turbidity was detected spectrophotometrically at 540 nm (Marangon et al, 2013). Differences in wine turbidity (before and after the heat treatment) have been shown to correlate directly to wine protein instability (Pachova, Ferrando, Guell, & Lopez, 2002).…”
Section: Protein Instability Testmentioning
confidence: 99%
“…Protein stabilisation using polysaccharides, such as carrageenans, is well established in the milk and brewing industries (Duan et al ). Previous reports of the addition of carrageenans to white wine and grape juice for haze stabilisation have shown that they can be effective when added either during wine processing or to the finished wine (Cabello‐Pasini et al , Marangon et al , ). Carrageenans are naturally occurring polysaccharides extracted from red seaweeds of the Rhophyta species (Necas and Bartosikoya ) and are therefore a potential renewable heat‐stabilising agent.…”
Section: Introductionmentioning
confidence: 99%